AB0132 Presence of Synovial Lymphocyte Aggregates Correlates with A More Severe Clinical Phenotype in Patients with Early Inflammatory Arthritis. (10th June 2014) - Di Cicco, M.; Humby, F.; Kelly, S.; Ng, N.; Mahto, A.; Hands, R.; Rocher, V.; Bombardieri, M.; Pitzalis, C.
Abstract : Background: Although many observations have suggested that ectopic lymphoid structures within the inflamed synovium are immunologically functional and can support chronic inflammation, their clinical significance is still controversial. Moreover, most of data comes from patients with long standing disease activity, while data in early arthritis is still scarce. In particular, it is unclear whether the presence of lymphocytic aggregates within the synovium correlates with clinical phenotype and degree of inflammation in early inflammatory arthritis patients. Objectives: The aim of this study is to evaluate the correlation between synovial lymphocytic aggregates with clinical phenotype in an early inflammatory arthritis cohort. Methods: 155 disease-modifying antirheumatic drug-naïve patients with early inflammatory arthritis (<12 months duration, at least 1 swollen joints) has been recruited at Barts and The London Hospital. Baseline disease characteristics assessment included erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) level, rheumatoid factor (RF), anti-cyclic-citrullinated peptide (CCP) and 28 joints-disease activity score (DAS28). Ultrasound-guided synovial biopsy has been obtained for all patients. Sections of paraffin embedded synovial tissue were stained with standard Haematoxylin and Eosin (H&E) and graded as either a diffuse or aggregate synovitis. The degree of lymphoid organisation was further assessed by immnohistochemical staining of sequentially cut sections. The number of lymphocytic aggregates was counted in each section and graded according to a validated, previously published grading system [Manzo, A. et al; European Journal of Immunology2005]. Results: The presence of lymphocytic aggregates has been found in almost 30% of patients; Lymphocytic aggregates are associated with increased inflammatory markers and DAS28, as well as RF and CCP seropositivity (p<0.05); The number of B cells and plasma cells in the synovium of early rheumatoid arthritis patients is closely associated (p<0.05), suggesting in situ differentiation. Conclusions: The presence of lymphocytic aggregates within the synovium in early arthritis correlates with a more severe clinical phenotype, including inflammatory markers, disease activity and antibody status. Further studies are needed in order to establish the clinical relevance of this association, and in particular its potential prognostic value. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5836